Edukasi Nilai Nilai Lokal Wisdom untuk Pembentukan Karakter Cinta Damai pada Siswa Sekolah Dasar: Pengabdian - Kamarudin; Akbar, Azaz; Kosilah; Masri; Syamsurijal; Manan; Sumantri, Sri; Suarti; Agusalim; Hadi Fahmi Bahari, Nur (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This article is the result of community service activities carried out collaboratively by students, teachers, and lecturers of the University of Muhammadiyah Buton through the School Field Introduction (PLP) 2 program at SD Negeri 1 Wameo. The purpose of this activity is to instill and internalize the values of local wisdom as the basis for the formation of peace-loving character in elementary school students. The implementation method includes three main stages, namely: (1) character development through an educational approach, (2) application of local values through interactive and contextual activities such as role-playing, and (3) strengthening and interpreting character through reflection and habituation. The local values raised are sourced from the Buton cultural philosophy, namely PO-5: Pomaamaasiaka (loving each other), Popiapiara (caring for each other), Pomaemaeka (mutual respect), Poangka-angkata (raising each other's dignity), and Pobincibinciki (caring for each other's feelings). The results of the activity showed that students not only understood grades cognitively, but were also able to experience them emotionally and socially in daily life. This activity proves that an approach based on local wisdom can be an effective strategy in strengthening character education in elementary schools.